A proposed framework of e-customer satisfaction in China: E-service quality, trust, repurchase intention - Wang Zi Meng; Toh Pei Sung; Brahim Chekima (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
China's decision-making and deployment on accelerating the development of the digital economy in 2023 will promote e-commerce to play an important role in restoring and expanding consumption and promoting the integration of digital and real, and high-quality development will achieve positive results. Online retail sales for the whole year were 15.42 trillion yuan, an increase of 11%. The rivalry in China's e-commerce sector has increased along with the growth of the sector and the notable rise in merchant numbers. This research theoretically explores the characteristics of e-commerce on customer satisfaction, given that it is impacted in this context. The evaluated literature identifies crucial elements and problems to establish a research framework for this article's upcoming empirical studies.